Zeit und Geld im Lebensverlauf - Empirische Evidenz und sozialpolitischer Handlungsbedarf aus der Geschlechterperspektive (Time and Money in the Life Course - Empirical Evidence and Implications for Social Policy from a Gender Perspective) - Ute Klammer (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2007)
– The article analyses the distribution of time and money from a life-course perspective, focussing on differences between women and men. Using different available data-sources, characteristic patterns of female and male life courses and their changes over time are being discussed. The article also compares the German patterns with patterns from other European countries. In the second part, social policy measures and company strategies that could contribute to a gender-sensitive life-course approach in social protection are developed and discussed.
Keywords: J11; J16; J13; J22; L53; I30; 330; social security; employment security; gender; time allocation; employment income; flexicurity; international comparison